Evaluation of graphic brands developed with a targeted method by specialists through informational ergonomics - da Silva, João Carlos Riccó Plácido [UNESP]; Paschoarelli, Luis Carlos [UNESP]; Friso, Valéria Ramos [UNESP]; da Silva, José Carlos Plácido [UNESP] (Springer Nature, 2019)
The graphic development, facilitated by digital tools, has allowed the growth of arbitrary forms of graphic representation and application, whether printed or digital, that cause errors of communication and understanding of them. The processing of information by the human mind can be evaluated by the ergonomics of the information, allowing to evaluate the positive and negative aspects of the visual information. For this purpose, specific evaluation methods such as Delphi can be used. Thus graphic marks were developed by two study groups, one control and the other experimental. The first one developed without any specific method while the second one used a directed method to allow the later analysis of the specialists and to validate the method that was used in this step. The procedure consisted in the application of several questionnaires to a selected group of experts, using with the aim of obtaining a consensus. The results were demonstrated in infographics that confirmed that the use of a directed design method contains and presents to its end user more aspects requested in the briefing.
Keywords: DELPHI; Evaluation; Graphic brands; Informational ergonomics; Specialists; Targeted method